2017
DOI: 10.3892/mmr.2017.6681
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 silencing enhances hyperoxia-induced alveolar epithelial cell apoptosis via CHOP pathway

Abstract: Hyperoxia is one of the primary causes of bronchopulmonary dysplasia, which may occur in premature infants following supplemental oxygen therapy. Glucose regulated protein 78 (GRP78), which is a molecular chaperone located in the lumen of the endoplasmic reticulum (ER), has been reported to regulate hyperoxia‑associated ER stress. The role of GRP78 in lung epithelial cells during hyperoxia remains to be elucidated. In the present study, the A549 cultured human lung epithelial cell line was exposed to hyperoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…CHOP is a transcription factor involved in the ER stress response. The overexpression of CHOP induces apoptosis through downregulation of Bcl‐2 and upregulation of the pro‐apoptotic proteins like Bim, Bax and Puma . In our investigation, CHOP was rapidly induced by combination of sorafenib and betulinic acid.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…CHOP is a transcription factor involved in the ER stress response. The overexpression of CHOP induces apoptosis through downregulation of Bcl‐2 and upregulation of the pro‐apoptotic proteins like Bim, Bax and Puma . In our investigation, CHOP was rapidly induced by combination of sorafenib and betulinic acid.…”
Section: Discussionmentioning
confidence: 52%
“…The overexpression of CHOP induces apoptosis through downregulation of Bcl-2 and upregulation of the pro-apoptotic proteins like Bim, Bax and Puma. (45,46) In our investigation, CHOP was rapidly induced by combination of sorafenib and betulinic acid. We found that combined treatment with sorafenib and betulinic acid induced both caspase 9 and caspase 8 in A549 cells, suggesting that both mitochondrial-dependent and mitochondrial-independent factors were responsible for the apoptotic potential.…”
Section: Discussionmentioning
confidence: 67%
“…CHOP is the first identified protein that mediates ER stress‐induced apoptosis, and the role of this molecule in apoptosis has been extensively studied . It is widely accepted that Bcl‐2 is a pro‐survival protein and Bax is a pro‐apoptotic protein . Moreover, researchers demonstrated that CHOP sensitizes cells to ER stress by down‐regulating Bcl‐2 and up‐regulating Bax .…”
Section: Discussionmentioning
confidence: 99%
“…29 It is widely accepted that Bcl-2 is a pro-survival protein and Bax is a pro-apoptotic protein. 29,30 Moreover, researchers demonstrated that CHOP sensitizes cells to ER stress by down-regulating Bcl-2 and up-regulating Bax. 29,30 In this study, CHOP siRNA significantly blocked TNF-induced Bax expression and TNF-inhibited Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation